A population perspective to evidence based medicine: "evidence for population health". Issue 1 (1st January 2002) - Heller, R F; Page, J
Abstract : We explore the notion that the public health community could learn lessons from the success of evidence based medicine (EBM) and develop a public health counterpart called "Evidence for Population Health". While EBM focuses on individual patients, its public health counterpart would aim to improve the health of communities effectively and efficiently.